Preschool English teachers gaining bilingual competencies in a monolingual context. (July 2020) - Dikilitaş, Kenan; Mumford, Simon E.
Abstract: This study examines three preschool teachers' developmental journeys from Foreign Language to Bilingual English teachers who participated in an in-service training over the course of nine months set in preschool education in Turkey. The data were teachers' logs, two written interviews and observation notes. The research questions addressed the evidence for a developmental growth into bilingual teacher roles and examined how such development might influence these teachers. Adopting a longitudinal design, our study is informed by Benson's (2004) categories of BE teacher competencies but modified to fit an EFL context with no history of heritage/colonial language. The findings indicate teachers' roles of pedagogue, interactive communicator, and a previously uninduced role, translanguaging facilitator. In addition, we argue that these categories influence each other, because the theoretical pedagogical aspects and the practical language aspects inform each other. The evidence of growth into new bilingual teacher roles could offer implications for similar contexts, particularly by showing that kindergarten school teachers need to embrace and develop roles other than foreign language teacher.